Austral summer circulation in the Bransfield Strait based on SADCP measurements and satellite altimetry - Frey, Dmitry; Krechik, Viktor; Gordey, Alexandra; Gladyshev, Sergey; Churin, Dmitry; Drozd, Ilya; Osadchiev, Alexander; Kashin, Sergey; Morozov, Eugene; Smirnova, Daria (Frontiers in Marine Science, 2023)
Three-dimensional structure of currents in the Bransfield Strait (BS) was measured in 2017 over 50 transects across the strait using a Shipborne Acoustic Current Doppler Profiler (SADCP) onboard the R/V Akademik Sergey Vavilov and Akademik Ioffe. These data were used to determine local features of the three-dimensional velocity field of the currents. The sections crossed all three basins of the BS and the main flows in the strait including the Bransfield Current and the southwestward flow of Weddell Sea waters along the Antarctic Peninsula. Two vessels are equipped with different SADCP systems with frequencies of 76.8 kHz and 38.4 kHz, which allows us to compare the data from different SADCPs. The observations reveal that very dense waters from the Weddell Sea propagate in deep layers over the shelf break; this flow is usually not observed at the sea surface. Vertical structure of the Bransfield Current significantly differs from the flow of the Weddell Sea waters and its velocity maximum is located in the upper ocean layer. We also used two gridded altimetry products of 0.25° and 0.1° resolution for investigations of circulation in the BS. We analyzed the efficiency of satellite altimetry in reproducing currents in conditions of a narrow strait and evaluated its accuracy using field velocity observations. We found that satellite altimetry can be used for identification of the mean ocean circulation patterns within the BS. However, daily altimetry data contain significant discrepancies with the in situ data and require direct measurements for studies of the BS circulation.